One session of remote ischemic preconditioning does not improve vascular function in acute normobaric and chronic hypobaric hypoxia - Rieger, M. G.; Hoiland, R. L.; Tremblay, J. C.; Stembridge, M.; Bain, A. R.; Flück, D.; Subedi, P.; Anholm, J. D.; Ainslie, P. N. (Experimental Physiology, 2017)
Application of repeated short-duration bouts of ischaemia to the limbs, termed remote ischemic preconditioning (RIPC), is a novel technique that might have protective effects on vascular function during hypoxic exposures. In separate parallel-design studies, at sea level (SL; n = 16) and after 8-12 days at high altitude (HA; n = 12; White Mountain, 3800 m), participants underwent either a sham protocol or one session of four bouts of 5 min of dual-thigh-cuff occlusion with 5 min recovery. Brachial artery flow-mediated dilatation (FMD; ultrasound), pulmonary artery systolic pressure (PASP; echocardiography) and internal carotid artery (ICA) flow (ultrasound) were measured at SL in normoxia and isocapnic hypoxia (end-tidal math formula maintained at 50 mmHg) and during normal breathing at HA. The hypoxic ventilatory response (HVR) was measured at each location. All measures at SL and HA were obtained at baseline (BL) and at 1, 24 and 48 h post-RIPC or sham. At SL, RIPC produced no changes in FMD, PASP, ICA flow, end-tidal gases or HVR in normoxia or hypoxia. At HA, although HVR increased 24 h post-RIPC compared with BL [2.05 ± 1.4 versus 3.21 ± 1.2 l min-1 (% arterial O2 saturation)-1, P < 0.01], there were no significant differences in FMD, PASP, ICA flow and resting end-tidal gases. Accordingly, a single session of RIPC is insufficient to evoke changes in peripheral, pulmonary and cerebral vascular function in healthy adults. Although chemosensitivity might increase after RIPC at HA, this did not confer any vascular changes. The utility of a single RIPC session seems unremarkable during acute and chronic hypoxia